Olfactory and cortical projections to bulbar and hippocampal adult-born neurons - De La Rosa-Prieto, Carlos; De Moya-Pinilla, Miguel; Saiz-Sanchez, Daniel; Ubeda-banon, Isabel; Arzate, Dulce M.; Flores-Cuadrado, Alicia; Liberia, Teresa; Crespo, Carlos; Martinez-Marcos, Alino (Frontiers in Neuroanatomy, 2015)
New neurons are continually generated in the subependymal layer of the lateral ventricles and the subgranular zone of dentate gyrus during adulthood. In the subventricular zone, neuroblasts migrate a long distance to the olfactory bulb where they differentiate into granule or periglomerular interneurons. In the hippocampus, neuroblasts migrate a short distance from the subgranular zone to the granule cell layer of the dentate gyrus to become granule neurons. In addition to the short-distance inputs, bulbar interneurons receive long-distance centrifugal afferents from olfactory-recipient structures. Similarly, dentate granule cells receive differential inputs from the medial and lateral entorhinal cortices through the perforant pathway. Little is known concerning these new inputs on the adult-born cells. In this work, we have characterized afferent inputs to 21-day old newly-born neurons. Mice were intraperitoneally injected with bromodeoxyuridine. Two weeks later, rhodamine-labeled dextran-amine was injected into the anterior olfactory nucleus, olfactory tubercle, piriform cortex and lateral and medial entorhinal cortices. One week later, animals were perfused and immunofluorescences were carried out. The data show that projection neurons from the mentioned structures, establish putative synaptic contacts onto twenty-one-day-old neurons in the olfactory bulb and dentate gyrus, in some cases even before they start to express specific subpopulation proteins. Long-distance afferents reach middle and outer one-third portions of the molecular layer of the dentate gyrus and granule and, interestingly, periglomerular layers of the olfactory bulb. In the olfactory bulb, these fibers appear to establish presumptive axo-somatic contacts onto newly-born granule and periglomerular cells.